BALINESE AGRICULTURE IN A CHANGING WORLD - Sutjana, I.D.P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2008)
Agriculture has been and continues to be one of the economic foundations of Bali and to be a major livelihood for Balinese people. The wide of agricultural area or rice field to be a symbol of community prosperity. It is accepted that in the region which consists of wide of rice fields is considered as a rich region and their inhabitants consequently have a better standard of living, due to having enough food. Because the agricultural sector capable to enhance the community prosperity the people should give effort to own more rice field (build or bought). All of agricultural activities influenced the daily community activity and become community cultural as well as organization, work tool, household tool, value system, plant which are cultivated, ceremony etc. always related to the agriculture. Agricultural technology (machine or method) used by the Balinese farmers still simple and inherited from generation to generation. It seems to be no development or progress resulted in that